Efficiency of Renewable Energy Sources in Reducing Carbon Footprint in Developing Countries - Kamau, John (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to examine efficiency of renewable energy sources in reducing carbon footprint in developing countries Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study demonstrated the effectiveness of various renewable energy technologies, such as solar photovoltaic systems, wind power, biogas technology, and hydropower, in mitigating carbon emissions and promoting sustainable development. These technologies offer reliable, environmentally friendly alternatives to fossil fuels, contributing to enhanced energy access, reduced reliance on traditional biomass fuels, and positive socio-economic impacts. However, realizing the full potential of renewable energy requires addressing barriers such as upfront costs, financing constraints, and technical capacity limitations. Policy interventions play a crucial role in scaling up renewable energy deployment through targeted incentives, regulatory frameworks, and capacity-building initiatives. Unique Contribution to Theory, Practice and Policy: Technology Adoption Theory, Environmental Policy Theory & Energy Transition Theory may be used to anchor future studies on efficiency of renewable energy sources in reducing carbon footprint in developing countries. Implement practical measures to facilitate technology transfer and capacity building in renewable energy sectors. This involves partnerships between developed and developing countries to share knowledge, expertise, and resources for deploying and maintaining renewable energy infrastructure. Establish supportive regulatory frameworks that streamline permitting processes, ensure grid integration, and provide market access for renewable energy producers. Clear and consistent regulations create an enabling environment for renewable energy investments and facilitate the transition to low-carbon energy systems.